The Effects of Cigarette Smoking on Steroidal Muscular Relaxants and Antibiotics Used: A Prospective Cohort Study - Liu, Na; Wang, Feng; Zhou, Qian; Shen, Minhuan; Shi, Jing; Zou, Xiaohua (Frontiers in Pharmacology, 2021)
Background: The impact of cigarette smoking on perianesthesia management is not clear elucidated. This paper studies the impact of long-term cigarette smoking on the dose-response of rocuronium. Methods: We enrolled 240 participants from a teaching hospital in China—80 participants with long-term cigarette use and 160 participants without a history of smoking were included. All participants received general anesthesia for various surgeries, and rocuronium was used as the muscular relaxant. The primary outcome was the effective onset time of rocuronium after adjusting for its dose. The secondary outcomes included a recovery index and the time of muscle tremor changing from 25% to 75%. Results: There was no measurable difference in the muscle relaxant onset time, duration of effectiveness, 75% recovery, recovery index, dose of opiates, anesthetics during surgery, or complication rate between smokers or non-smokers. However, the results showed a significant difference in antibiotic use between smokers and non-smokers (chi-squared=13.695, P<0.001), and a significant difference in the type of antibiotics used (chi-squared=21.465, P= 0.003). Smokers had a significantly higher rate of cefathiamidine use. Conclusions: Smoking cigarettes had no effect on muscle relaxants used under general anesthesia, but patients who had a history of smoking were more likely to receive antibiotics after surgery.